MODEL SELECTION OF KRI CHANGE OF DEVELOPMENT TO SUPPORT THE MAIN TASKS OF THIRD FLEET USING THE MCDM INTEGRATION METHOD - Tunang Arimbo; Suparno Suparno; Ahmadi Ahmadi; Eko Krisdiono (JOURNAL ASRO, 2021)
Third Fleet is the Main Command of the Indonesian Navy as Operation City which is tasked with carrying out defense and security operations of the maritime dimension by securing the territorial waters of eastern Indonesia. The operation in these waters is faced with the vulnerability of frequent violations, geological conditions consisting of thousands of islands and shallow straits, extreme weather and also with limited state defense budget conditions. Therefore, it is very necessary to have a KRI that is right and ready to face these challenges and obstacles so that the goals of the organization can be achieved. The purpose of this study was to analyze the criteria and determine the type of KRI needed in accordance with the conditions in Third Fleet. This study uses an integration between the Delphi method and the AHP method. The results of this study are expected to be input and consideration for the leadership of the Indonesian Navy. The next 299 are fast boats with a weight value of 0.149 then Amfibious ships with a weight value of 0.154 then Bantu ships with a weight value of 0.131 then Mine ships with a weight value of 0.119 and Submarines with a value of 0.114. The results of this study are expected to be input and consideration for the leadership of the Indonesian Navy. Keywords: Third Fleet, Delphi, AHP